IMPORTANCE OF RECRUITMENT, SELECTION AND PLACEMENT ON PRODUCTIVITY - Ekeh, Fidelia Ifeoma (African Journal of Social and Behavioural Sciences, 2024)
The paper discusses the importance of recruitment, selection and placement on productivity. The paper identified the problem of the dire consequences of poor personnel recruitment and placement process in organisations marred by favouritism, prejudice, and exclusionism. The paper observed that recruitment, selection and placement form a major part of an organization’s overall resource strategies, which identify and secure people needed for the organization to survive and succeed in the short to medium term period. This paper aimed to show that recruitment, selection and placement activities need to be responsive to the everincreasingly competitive market to secure suitably qualified and capable recruits at all levels. As a position paper, adopting a conceptual analysis approach, the paper concludes that although technology has enabled massive personal productivity gains, however, if individuals are able to perform their work much better and faster, overall productivity will improve. It is recommended among other things therefore, that adequate attention should be paid to the recruitment, selection and placement processes in organisations so as to attract high quality manpower to improve productivity.